ANALISIS VARIASI NUKLEOTIDA DAERAH D-LOOP DNA MITOKONDRIA PADA SATU INDIVIDU SUKU BALI NORMAL - Ketut Ratnayani; I Nengah Wirajana; A. A. I. A. M. Laksmiwati (Jurnal Kimia (Journal of Chemistry), 2007)
Human mitochondrial DNA (mtDNA) has higher polimorfism level than nucleous genom, especially in theD-Loop region, which is a non coding region and the most polymorfic region in the mitochondrial genom. Theanalysis of variation of nucleotide sequence of D-Loop region can be used to determine the individual or ethnicidentity and also maternal familiar relationship. The research aims to determine nucleotide variant on Balineseindividue, which can be used as data base in determination of mtDNA genetical profile of Balinese ethnic in a biggerscale.To achieve the aims of the research, way the nucleotide sequence of one normal Balinese individue usingthe epithelia cells in the saliva. The methods were :1) the isolation of sample mtDNA, 2) the amplification of the DLoopregion of mtDNA by PCR, 3) sequencing and analysis of nucleotides sequence.The 0,4 kb fragment of the D-loop region mtDNA of the sample were successfully amplified, andsequenced of 402 pb. The research found 6 new variants or morfe different from Cambridge or Anderson sequence :variant 16223C®T, 16249T®C, 16259C®T, 16278C®T, 16316A®G, 16375C®A. The research also found thedeletion of T nucleotide on position 16362.